Valores de futuros engenheiros ambientais sobre o meio ambiente - Tonin, Ivone Borges da Costa [UNESP] (2015)
Environmental issues are among the topics that have received great attention and aroused the concern of contemporary society, in view of the need for environmental planning according to various imbalances caused by the development of modern society. Examining the work in the Environmental area, one can observe that still remain, in society in general, visions whose concepts are accompanied by a sense of control, supervision or inaccessible scenarios and unattainable to the individual. This perspective is influenced possibly by the view that the professionals themselves convey. This thesis aims to analyze the future environmental engineers design the environment. The analysis is focused on the prevailing values and the level of social perspective of decentralization (inspired by Kohlberg) obtained. With regard to the method, was performed a case study for which they were selected Environmental Engineering Academic course. The instrument used was a questionnaire consisting of four items. The sample comprised 39.2% of male participants and 60.8% female, the mean age was 23.5 years, the motivation for the choice of the course was predominantly related to interest and vocation and areas of intended action were related to water resources, water treatment and / or waste and environmental preservation and recovery of degraded areas. The economic classification showed that prevail students of economy class B (62.4%). The specific questions showed that 95.2% of respondents said they were involved in the preservation of the environment and 32% have already developed or developing work in environmental education. The analysis of Likert Scale showed that most of the academics is geared to a system of ecocentric values, scientific, emotional and ethical / social and environmental, and does not agree with anthropocentric and instrumental values. In the first vignette is observed that the value of the studied group ecocentric prevailed. In the second...